FRAMING WATER SCARCITY IN SOUTH ASIA: A COMPARATIVE ANALYSIS OF PAKISTANI AND INDIAN MEDIA (Contemporary Journal of Social Science Review, 2025)
Water scarcity poses a severe and escalating threat in South Asia, particularly in Pakistan and India, where climatic instability, rapid population growth, and political tensions intensify resource insecurity. This study investigates how mainstream media in the two countries frame water scarcity and how these framing practices shape public perceptions and responsibility attribution. Using qualitative content analysis of 300 media texts and 40 semi-structured interviews, the study compares episodic and thematic framing, responsibility narratives, emotional tone, and representation of affected communities. Results show that episodic framing dominates coverage, particularly in Pakistani media, promoting reactive crisis narratives and individual or external blame attribution. Indian media adopt thematic framing more frequently, emphasizing developmental reforms and governance challenges. Pakistani media engage more strongly in conflict and nationalism framing, while Indian narratives highlight modernization solutions. Both media systems marginalize voices of affected communities. Findings illustrate that framing strategies significantly influence public understanding, emotional response, and policy expectations. The study argues for more thematic, inclusive, and cooperative framing practices to support sustainable environmental governance and regional stability.